(untitled) (Research, Society and Development, 2021)
Dengue is a major public health problem, which mainly affects the population of tropical and subtropical regions in the world, in addition to the thousands of travelers who visit these areas. Transmission occurs through the bite of female vectors of Aedes aegypti, Aedes albopictus, Aedes scutellari or Aedes polynesiensis, infected by the virus, which can lead to manifestations ranging from asymptomatic to hemorrhagic fever. Thus, the study carried out is an integrative literature review, described as a research method that allows for the search, critical evaluation and synthesis of available evidence on the topic investigated, being used twenty articles to carry out the same. Thus, dengue can be manifested in different ways, from asymptomatic infection to undifferentiated fever, dengue hemorrhagic fever or dengue shock syndrome. Therefore, the importance of detailed knowledge of all manifestations that can affect the patient with dengue is highlighted, in addition to performing a very detailed clinical examination, making use of complementary means for diagnosis, such as exams. Time is essential at this time, as it can favor the patient’s prognosis, avoiding future complications.